Kondycja prasy lokalnej 18 lat po powstaniu gazety „ABC” w Lesznie - Klak, Paweł (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
According to macroeconomic principles, the Polish local press should no longer exist at the time of globalization and capital concentration, and yet it is coping somehow. Is it actually true though that it remains independent, in defiance of global trends? Or maybe it is simply becoming a local variety of an increasingly uniform, ‘globalized’ product? It is best to look for the answers to these and similar questions with the example of one, real newspaper. The ABC newspaper is published by the Przedsiębiorstwo Usług Handlowo-Produkcyjnych i Wdrożeń Polrex Spółka z o.o., established on October 24, 1990, with its Head Office at 15 OEl1ska St. in Poznan. The partnership managed by editor Szczepan Lawniczak was established in order to register a Leszno newspaper ABC – Dziennik Informacyjny with its Head Office at 68 Lipowa St. in Leszno. After only four months, on February 25, 1991, a significant change in the newspaper’s registration was introduced. A company, Przedsiębiorstwo Przemysłu Fermentacyjnego Akwawit in Leszno, submitted a motion for a change on behalf of a limited liability company which it had established, Leszczynska Oficyna Wydawnicza, with its Head Office at 63 S3owianska St. in Leszno. Since then, this very company has become an official publisher of the ABC – Dziennik Informacyjny. An employee company, Leszczyńska Oficyna Wydawnicza, has been the only publisher of the ABC newspaper so far.